Transcriptome and molecular regulatory mechanisms analysis of gills in the black tiger shrimp Penaeus monodon under chronic low-salinity stress - Li, Yun-Dong; Si, Meng-Ru; Jiang, Shi-Gui; Yang, Qi-Bin; Jiang, Song; Yang, Li-Shi; Huang, Jian-Hua; Chen, Xu; Zhou, Fa-Lin; Li, ErChao (Frontiers in Physiology, 2023)
Background: Salinity is one of the main influencing factors in the culture environment and is extremely important for the survival, growth, development and reproduction of aquatic animals. Methods: In this study, a comparative transcriptome analysis (maintained for 45 days in three different salinities, 30 psu (HC group), 18 psu (MC group) and 3 psu (LC group)) was performed by high-throughput sequencing of economically cultured Penaeus monodon. P. monodon gill tissues from each treatment were collected for RNA-seq analysis to identify potential genes and pathways in response to low salinity stress. Results: A total of 64,475 unigenes were annotated in this study. There were 1,140 upregulated genes and 1,531 downregulated genes observed in the LC vs. HC group and 1,000 upregulated genes and 1,062 downregulated genes observed in the MC vs. HC group. In the LC vs. HC group, 583 DEGs significantly mapped to 37 signaling pathways, such as the NOD-like receptor signaling pathway, Toll-like receptor signaling pathway, and PI3K-Akt signaling pathway; in the MC vs. HC group, 444 DEGs significantly mapped to 28 signaling pathways, such as the MAPK signaling pathway, Hippo signaling pathway and calcium signaling pathway. These pathways were significantly associated mainly with signal transduction, immunity and metabolism. Conclusions: These results suggest that low salinity stress may affect regulatory mechanisms such as metabolism, immunity, and signal transduction in addition to osmolarity in P. monodon. The greater the difference in salinity, the more significant the difference in genes. This study provides some guidance for understanding the low-salt domestication culture of P. monodon.